Preserving Cultural Heritage Through Community Participation: An Action Research Study on Local Cultural Engagement Initiatives - Roisul Basyar; Thotham Thotham (CV. Zabags Qu Publish, 2026)
Preserving cultural heritage has become a pressing challenge in the context of globalization, urbanization, and the rapid advancement of digital technologies. This study aims to analyze the forms, characteristics, and levels of community participation in local cultural preservation initiatives, while also developing strategies based on participatory approaches through the application of Participatory Action Research (PAR). Employing a qualitative participatory design, the research actively engaged communities in iterative cycles of problem identification, planning, action, observation, and reflection. Data were collected through in-depth interviews, participatory observation, focus group discussions, documentation, and institutional records. The findings reveal that community participation manifests in direct involvement in cultural activities, the pivotal role of traditional leaders and cultural organizations, and the contribution of younger generations through digital documentation and promotion. Supporting factors include strong community leadership, local government support, and robust social networks, while barriers involve limited funding, low cultural awareness among youth, and weak stakeholder coordination. This study contributes to the development of a participatory and sustainable model of cultural preservation that can be replicated across diverse local communities. It also enriches academic discourse by integrating theories of community participation, social capital, empowerment, and cultural heritage within the methodological framework of Action Research, offering both theoretical insights and practical implications for sustainable cultural preservation.